Diálogos entre a justiça restaurativa e o direito socioeducativo brasileiro no tratamento de adolescentes em conflito com a lei - Natália de Souza Neves (2014)
This dissertation aims at understanding Restorative Justice as an effective and differentiated way of solving conflicts to be used with adolescents who have commited offences. In contrast to the retributive system, which focus on guilt and punishment, centered on bygone acts, Restorative Justice proposes, through a dialogical process, based on alterity, respect and recognition of the other, to correct, to the extent possible, the damage caused to the victim by the ofender. Aiming to establish an interface between Children and Adolescents’ legal system and Restorative Justice, to base its use with adolescentes who have commited offences, an analysis of Brasilian Children and Adolescent’s legal system was made, under the doctrine of integral protection. This analysis was made in order to seek theoretical and legal support to justify the use of restorative practices in juvenile justice. It’s very much important, in Restorative Justice, the necessities of the adolescent who have commited the offence. There are adolescents who are often deprived of their fundamental rights, in a situation of social vulnerability, with restricted access to education, health, labor, among others. Therefore, it’s useful to highlight the interdisciplinarity of Children and Adolescents’ legal system, which foundation on the doctrine of integral protection and treatment throught network envision the supply of opportunities to the adolescent who commited the offence, so that he has access to other possibilities, not juvenile delinquency. To illustrate this work, a case study in which the proposal of Restorative Justice was used with adolescents who commited offences was carried out. Thus, interviews were contucted with operators of the Childhood and Youth Justice System working in the CIA (Integrated Center of treatment of adolescents who commited offences). These interviews aimed at understanding the process of implementation of Restorative Justice in CIA, the difficulties experienced in this process, as well as the perspectives of the respondents regarding this method of resolution of conflicts.